Semi-quantitative CT score reflecting the degree of pulmonary infection as a risk factor of hypokalemia in COVID-19 patients: a cross-sectional study - Li, Ru; Wu, Baofeng; Yang, Xifeng; Liu, Botao; Zhang, Jian; Li, Mengnan; Zhang, Yi; Qiao, Ying; Liu, Yunfeng (Frontiers in Medicine, 2024)
Background Hypokalemia is a common electrolyte disorder observed in patients afflicted with coronavirus disease 2019 (COVID-19). When COVID-19 is combined with a pulmonary infection, chest computed tomography (CT) is the preferred diagnostic modality. This study aimed to explore the relationship between CT semi-quantitative score reflecting the degree of pulmonary infection and hypokalemia from COVID-19 patients. Methods A single-center, cross-sectional study was conducted to investigate patients diagnosed with COVID-19 between December 2022 and January 2023 who underwent chest CT scans upon admission showing typical signs. These patients were categorized into two groups based on their blood potassium levels: normokalemia group and hypokalemia group. Medical history, symptoms, vital signs, laboratory data and CT severe score were compared. Binary regression analysis was employed to identify risk factors associated with hypokalemia in COVID-19 patients with pulmonary infection. Results A total of 288 COVID-19 patients with pulmonary infection were enrolled in the study, of which 68 (23.6%) patients had hypokalemia. In the hypokalemia group, there was higher CT severity score than the normokalemia group [4.0(3.0-5.0)vs3.0(2.0-4.0), p=0.001]. The result of binary logistic regression analysis revealed that after adjusting for sex, vomiting, sodium and using potassium-excretion diuretics, higher CT severity score was an independent risk factor for hypokalemia (OR=1.229, 95%CI=1.077-1.403, p=0.002). Conclusions In this cohort of patients, semi-quantitative CT score reflecting the degree of pulmonary infection could be used as a risk factor of hypokalemia in COVID-19 patients.